Global perspectives on crime prevention and community resilience: International Police Executive Symposium - Scharff Peterson, Diana; Das, Dilip K. (International Police Executive Symposium co-publications, 2019)
Acknowledgments -- Introduction -- Global strategies for crime and violence prevention -- Coordinated community response to domestic violence and sexual assault on the college / ROBERT HANSER -- Different communities, different approaches : avoiding a "one size fits all" approach to neighborhood policing strategies / MIKE PERKINS -- Community-based participatory approach to prevent residential burglaries and house robberies / DORAVAL GOVENDER -- Crossing the great divide : the development and effectiveness of working relationships between law enforcement personnel and academic researchers / LIN HUFF-CORZINE & JAY CORZINE -- The B3W matrix : managing a more effective way to tackle residential burglary / PETER VERSTEEGH & RENE HESSELING -- Building resilience and engaging communities for violence and crime prevention -- Managing language barriers in policing / SEDAT MULAYIM & MIRANDA LAI -- Community policing and vigilantism : two alternative strategies for fighting neighborhood crime / BRUNO MEINI -- Policing in remote australia : is it possible to ignore colonial borderlines? / JUDY PUTT & RICK SARRE -- Multi-sector cooperation in preventing crime : the case of south african neighborhood watch as an effective crime prevention model / JOHAN VAN GRAAN -- Assisting special populations, women and crime victims -- Human trafficking : a global examination of sexual exploitation, corruption, and future implications / TIFFINEY BARFIELD-COTTLEDGE; CYNTHIA HERNANDEZ; JOSE CERVANTES; ATTAPOL KUANLIANG & OCTAVIA S. BOLTON -- Building community resilience : strategic role of police with bombing victims / ZORA SUKABDI -- Women in criminal justice : reality or myth / CHRISTIAAN BEZUIDENHOUT -- Strategies in prevention of crime against women in india-with special reference telangana state / ADKI SURENDER -- The assessment of capable guardianship measures against bullying victimization in the school environment / KYUNG-SHICK CHOI; SHEA CRONIN & HEATHER CORREIA -- Promoting best practices for police officer safety, accountability, effectiveness, professionalism and retention -- An analysis of the effects of on-body officer camera systems / LEE RANKIN -- Information sharing in the investigative units of local law enforcement agencies : which unit shares information and why? / BLAKE M. RANDOL -- Retention factors in relation to organizational commitment : empirical evidence from ghana police service / GERALD DAPAAH GYAMFI -- Safety management and performance-based management : an excellent match / PAUL VAN MUSSCHER & PETER VERSTEEGH -- Index --